The application of choice modelling for a sanitary landfill in Kota Bharu, Kelantan, Malaysia - Nik Ab Rahim, Nik Nor Rahimah; Othman, Jamal; Yacob, Mohd Rusli (Malaysian Institute Of Planners, 2024)
Environmental impacts from poor landfilling practices have long been a concern in Kota Bharu, a densely populated city in Peninsular Malaysia. Addressing this issue requires a sustainable disposal solution, such as a sanitary landfill. However, such a project can fail without understanding household demand. This study examined households' willingness to pay for a sanitary landfill using a survey-based method known as Choice Modelling. This method was employed to determine households' willingness to pay for the environmental benefits of a sanitary landfill, characterized by attributes like controlled leachate discharge, reduced bad odour, reduced disease vectors, and pleasing views. The results indicated a positive willingness to pay for each attribute, ranging from RM2.37 to RM12.08 per month. This information aids policymakers in making decisions that align with household demands, thereby minimizing opposition and enhancing project feasibility.